CHOOSING INDONESIA OVER ENGLISH-SPEAKING NATIONS: INTERNATIONAL STUDENTS’ PURSUIT OF EFL TEACHING QUALIFICATION - Lestari, Tri Puja; Silvhiany, Sary; Inderawati, Rita (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
The study examines the decision making process of international students opting to pursue graduate level education in non- English-speaking country, Indonesia, to become English as a Foreign Language (EFL) Teachers. Through a narrative approach, data was collected by using semi structured interviews with international students from diverse cultural background; South Korea, Brazil, and Mexico. The findings indicate that the ambitions of the international students are influenced by a combination of intrinsic motivations, including personal growth and cultural interest, as well as extrinsic factors such as career prospects, educational quality, and living environment. This analysis examines the impact of Indonesia's educational standards, cultural and geographical attractions, and career advancement opportunities on the decision-making processes of international students. The study indicates that international students perceive Indonesia as a favourable destination for EFL career development. It also identifies opportunities for institutions to better support these students by addressing their specific needs and improving employment pathways after graduation. The findings highlight Indonesia's increasing attractiveness as a destination for international EFL educators and indicate that promoting educational exchange can enhance international cooperation and contribute to the professional development of future teachers. Future research may investigate the educational experiences of international students from varied undergraduate backgrounds to enhance understanding of their journeys toward becoming educators in a global context.